Direito e desenvolvimento: as ações afirmativas nas universidades federais brasileiras sob a perspectiva da jurisprudência - Dominguez, Guilherme Diniz de Figueiredo (2010)
This paperwork is the result of a research that intends to investigate possible relations between Law and development, based upon an empiric study of the affirmative actions implemented by the Brazilian federal universities, mainly by means of the reservation of enrollment slots to minorities on its admission exams (social and racial quotas), but through the perspective of Court s decisions on the matter. The research focused on the analysis of whether or not such affirmative actions were held constitutional by the Regional Federal Courts of Brazil and by the Brazilian Supreme Court. Also the research intended to verify if such Courts recognized these quotas as public policies or affirmative actions (and thus if this recognition made them adopt a more detailed judicial review of such programs). Furthermore the research intended to study how the apparent conflict between the Executive Branch (universities) and the Legislative Branch, on whether a specific law is needed in order to authorize the adoption of such affirmative actions, was settled and how Courts acted when called to impose affirmative actions in the event of an omission by the Executive Branch. In addition to these specific issues, and assuming that affirmative actions are State policies directed to assure equality and, thus, reduce poorness and prejudice, aiming to promote social development, the main purpose of the research was to examine if such elements were part of the judicial debate that was studied and what was its importance on the examined decisions. We have verified that, considering absolute numbers, the quotas affirmative action is held constitutional by Federal Courts in Brazil. But by analyzing the decisions in each region of the Country we have noticed that a consensus on the subject is far and that there is no precedent of the Brazilian Supreme Court on the matter. In general, the Court s decisions value university autonomy on the implementation of affirmative actions, recognizing that such attribution does not belong only to the Legislative Branch, assessing such measures as public policies (and eventually, in more cases than anticipated, establishing or modulating these policies), although this assessment does not imply a deeper judicial review of the quotas programs, examining all its aspects. Beyond the debate on the constitutionality of the studied affirmative actions, the research detected a number of other problems related to its application, such as, for instance, the lack of a general and common provision on who could be considered a student from a public school in order to benefit from the social quotas, what suggests the need for a federal law determining the guidelines (standards) in order for such affirmative actions to be adopted by the federal universities in Brazil. Nonetheless, the debate on the constitutionality of such policies is marked by a clear discussion on its contribution or not to the development of the Country and, although that is not the main issue discussed on the decision, it is a strong element on the appreciation of the matter